Study on Two Unbound Granular Materials Stiffness Analysis with Staged Repeated Load CBR Test - Salmi, Abdelaziz; Bousshine, Lahbib; Lahlou, Khaled (Advanced Aspects of Engineering Research Vol. 1, 2021)
In many countries, the design methods of flexible pavements are based on linear elastic behavior model for Unbound Granular Materials (UGM). In this context, the parameters required to characterize an UGM in structural analysis of these pavements are stiffness modulus and Poisson ratio (E and v). This paper presents a study of two UGM stiffness in which Finite element simulation of repeated load CBR (RL-CBR) test has allowed to derive the equation used in calculation of equivalent modulus, based on laboratory RL-CBR Outputs. Meanwhile, the staged RL-CBR test is used to evaluate material stiffness for different stress levels in order to highlight its influence on UGM stiffness and compare studied materials at the same time. As a result, this study shows that even if two materials are different according to the current road authority specifications, they can represent similar stiffness.